Internalisasi Nilai-Nilai Pendidikan Agama Islam dalam Membentuk Karakter Peserta Didik Madrasah Tsanawiyah Negeri 1 Karawang - Nisrina Nur Chiari; Nurfalah, Yasin (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
The internalization of PAI values in the madrasah environment should have been well integrated and can affect the formation of the students’ character. most of the focus of learning campaigns is on the curriculum used and implemented. However, the hidden curriculum is also an important part of supporting the success of internalizing the PAI value and building character. The focus of this research is (1) How is the design internalization of ​​PAI values? (2) What are the implications for all aspects of the hidden curriculum? (3) How does the internalization ​​of PAI values through the hidden curriculum influence the formation of the students’ character? This study used a descriptive qualitative research type and used a field research approach. The research results show the hidden curriculum helps the process of internalizing PAI values in building the students’ character by transforming values through subjects of fiqh, al-Qur'an hadith, history of Islamic culture, and moral principles. And programs that train students such as the 3S program, midday prayers in congregation, rewards and punishments, etc. as well as through social interactions that occur in madrasas are examples from educators such as good educator habits.